A Transdisciplinary Approach Towards Studying Direct Mortality Among Demersal Fish and Benthic Invertebrates in the Wake of Pulse Trawling - Schram, Edward; Molenaar, Pieke; de Koning, Susan; Rijnsdorp, Adriaan D. (Frontiers in Marine Science, 2022)
Between 2009 and 2020, beam trawlers in the North Sea switched to electrical stimulation to target sole (Solea solea). The transition to pulse trawling raised widespread concern about possible adverse effects of electrical stimulation on marine organisms. Environmental NGO’s and small scale fishers claimed that it would electrocute marine life and create a ‘graveyard’ in the wake of pulse trawlers. This paper uses realistic field experiments to investigate the ‘graveyard’ hypothesis. In cooperation with fishers , a field experiment was designed where we simultaneously sampled marine organisms in the wake of pulse trawlers and in untrawled control areas. The impact was quantified by estimating the direct mortality among three dominant fish species and four dominant invertebrate species. In total, nine experimental tows were conducted in two years. Direct mortality among fish and invertebrates was low (0-10%) and did not differ between the pulse trawl track and the untrawled controls. Equally, no impact of the pulse trawl was found on external damages and vitality scores. The limited effects observed are likely due to the mechanical impact of the pulse and the sampling gear. The results of experiment do not support the claim that pulse trawling results in mass mortality among marine organisms in the trawl track. Throughout the research period, the concerns of small-scale fishers on pulse fishing shifted from being focused on biological effects to political and managerial issues. This can partly be attributed to the engagement in and the results of our research and has increased its credibility and salience. By integrating fishers’ knowledge and examining their perceptions through transdisciplinary research, we were able to show the importance of untangling the intricate relation between perceived knowledge gaps and political or management related concerns.